Linking the T cell receptor to the single cell transcriptome in antigen‐specific human T cells. Issue 6 (8th March 2016) - Eltahla, Auda A; Rizzetto, Simone; Pirozyan, Mehdi R; Betz‐Stablein, Brigid D; Venturi, Vanessa; Kedzierska, Katherine; Lloyd, Andrew R; Bull, Rowena A; Luciani, Fabio
Abstract : Heterogeneity of T cells is a hallmark of a successful adaptive immune response, harnessing the vast diversity of antigen‐specific T cells into a coordinated evolution of effector and memory outcomes. The T cell receptor (TCR) repertoire is highly diverse to account for the highly heterogeneous antigenic world. During the response to a virus multiple individual clones of antigen specific CD8+ (Ag‐specific) T cells can be identified against a single epitope and multiple epitopes are recognised. Advances in single‐cell technologies have provided the potential to study Ag‐specific T cell heterogeneity at both surface phenotype and transcriptome levels, thereby allowing investigation of the diversity within the same apparent sub‐population. We propose a new method (VDJPuzzle) to reconstruct the native TCRαβ from single cell RNA‐seq data of Ag‐specific T cells and then to link these with the gene expression profile of individual cells. We applied this method using rare Ag‐specific T cells isolated from peripheral blood of a subject who cleared hepatitis C virus infection. We successfully reconstructed productive TCRαβ in 56 of a total of 63 cells (89%), with double α and double β in 18, and 7% respectively, and double TCRαβ in 2 cells. The method was validated via standard single cell PCR sequencing of the TCR. We demonstrate that single‐cell transcriptome analysis can successfully distinguish Ag‐specific T cell populations sorted directly from resting memory cells in peripheral blood and sorted after ex vivo stimulation. This approach allows a detailed analysis of the TCR diversity and its relationship with the transcriptional profile of different clones.